Changes in Breathing Patterns of Patients with COPD Exacerbation After Nebulization at the Pulmonary Outpatient Clinic of RSUD Kabupaten Kediri - Francisca Rizky Yuniar; Yuly Peristiowati (Journal of Health Science Community, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung disease characterized by persistent airflow limitation. COPD exacerbation often causes increased dyspnea, respiratory rate, and decreased oxygen saturation, leading to an ineffective breathing pattern. This study aimed to determine changes in the breathing pattern of patients with COPD exacerbation after nebulization therapy at the Pulmonary Outpatient Clinic of RSUD Kabupaten Kediri. This study used a descriptive case study design involving five patients with COPD exacerbation. Data were collected through direct observation before and after nebulization using respiratory rate (RR), oxygen saturation (SpO₂), and the Borg CR10 Scale to assess the level of dyspnea. The results showed a decrease in respiratory rate and Borg score, as well as an increase in oxygen saturation in all patients after nebulization. In conclusion, nebulization provides a positive response in improving the breathing pattern of patients with COPD exacerbation in the outpatient setting.